2013
DOI: 10.1002/jts.21774
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With the Initial Police Response and Development of Posttraumatic Stress Disorder Symptoms in Victims of Domestic Burglary

Abstract: The current study used a prospective design to investigate the association between early symptoms, satisfaction with the initial police response, and development of posttraumatic stress disorder (PTSD) symptomatology in victims of domestic burglary (n = 95). Early symptoms and satisfaction with the initial police response were assessed through telephone interviews conducted within the first month after the burglary and PTSD symptoms 4 to 6 weeks after baseline. Separate regression models were tested for satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…To date, this seems to have been done only once before. Kunst, Rutten, and Knijf () found that crime victims who suffered from early PTSD symptoms during the first 2 weeks after the crime were at an increased risk of PTSD symptom increase 4 to 6 weeks later if they were not satisfied with the police response. However, this study only included victims of domestic burglary and did not distinguish between peri‐ and posttraumatic responses to the crime.…”
Section: Discussionmentioning
confidence: 99%
“…To date, this seems to have been done only once before. Kunst, Rutten, and Knijf () found that crime victims who suffered from early PTSD symptoms during the first 2 weeks after the crime were at an increased risk of PTSD symptom increase 4 to 6 weeks later if they were not satisfied with the police response. However, this study only included victims of domestic burglary and did not distinguish between peri‐ and posttraumatic responses to the crime.…”
Section: Discussionmentioning
confidence: 99%
“…They first asked subjects of the general population of the state of Kentucky to indicate whether they had been criminally victimized during a particular period and then asked them to comment upon the performance of the criminal justice system in their cases. All remaining studies used various types of convenience sampling to select participants, including recruitment via police departments (Frazier & Haney, 1996; Kunst, Rutten, & Knijf, 2013; Miller, 2003), public prosecution offices (Tontodonato & Erez, 1994), courts (Wemmers, 2013), victim/witness programs (Amick-McMullan, Kilpatrick, Veronen, & Smith, 1989), local crime victims’ rights organizations (Amick-McMullan et al, 1989), domestic violence intake centers (Bennett, Cattaneo, & Goodman, 2010), compensation funds (Kunst, 2011; Laxminarayan, 2012, 2013a, 2013b), victim support agencies (Laxminarayan, 2012; Orth, 2002, 2004 [studies 15a and 15b]; Orth & Maercker, 2004 [studies 16a and 16b]; Orth & Maercker, 2009), sexual assault referral centers (Maddox, Lee, & Barker, 2011), counseling agencies (Regehr, Alaggia, Lambert, & Saini, 2008), medical examiner offices (Thompson, Norris, & Ruback, 1996), and advertisements or presentations (Campbell et al, 1999; Campbell, Wasco, Ahrens, Sefl, & Barnes, 2001; Maddox et al, 2011; Regehr et al, 2008; Walsh & Bruce, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies succeeded in obtaining an adequate response rate (Frazier & Haney, 1996; Norris & Thompson, 1993). Fourteen studies failed to obtain an adequate response rate (Bennett et al, 2010; Kunst, 2011, Kunst et al, 2013; Laxminarayan, 2012, 2013b; Orth, 2002, 2004 [studies 15a and 15b]; Orth & Maercker, 2004 [studies 16a and 16b]; Orth & Maercker, 2009; Thompson et al, 1996; Tontodonato & Erez, 1994; Wemmers, 2013), while five other studies could not calculate response rates due to sampling method (Campbell et al, 1999, 2001; Maddox et al, 2011; Regehr et al, 2008; Walsh & Bruce, 2011). Three studies did not provide any information on response rates (Amick-McMullan et al, 1989; Laxminarayan, 2013a; Miller, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The programme evaluation would additionally teach us that it is not so much victim impact statement delivery per se that promotes victims´emotional recovery from the crime, but rather their satisfaction with how they were treated by other participants of the criminal proceedings during the court hearing (cf. ; see also Kunst, Rutten, & Knijf, 2013). -The process evaluation by Lens et al (2010) would teach us that victim impact statement delivery in Dutch courts usually occurs after substantial lapse of time; on average, study participants who had delivered a victim impact statement did so 17 months post victimisation.…”
Section: An Examplementioning
confidence: 99%